Surface and interfacial microstructure evolution of isothermally oxidized thermal barrier coating system - Karthiga Parthiban; Sandip Bykash; Sumana Ghosh (Results in Surfaces and Interfaces, 2024)
Novel multilayer functionally graded thermal barrier coating (TBC) system consisting of a newly developed glass-ceramic based bond coating, glass-ceramic-25% yttria stabilized zirconia (YSZ) composite coating and 100% 8-YSZ top coating. Since TBC is a layered system property matching between each layer is a major concern. Therefore, thermal properties of the developed glass-ceramic coating and composite coating were studied in detail. The developed system was exposed to static oxidation at 1100 °C for 100 h. To assess the efficacy of the TBC system, XRD phase analysis and also mechanical properties like Young's modulus and nanohardness was performed at each layer for both before and after isothermal oxidation. From the surface and interfacial microstructure evolution it was observed that there was crack development at composite coating-top coating interface, which was due to zirconia phase transformation from tetragonal to monoclinic crystal structure, confirmed by the presence of monoclinic zirconia XRD diffraction peaks in XRD analysis. Additionally, Raman spectroscopy was also carried out on the isothermally oxidized specimen, which also pointed out the presence of monoclinic crystal structure. Even though developed TBC system failed to protect the nimonic alloy (AE435) substrate from thermal exposure at 1100 °C for 100 h the glass-ceramic/substrate had a good interfacial adhesion. Main advantage of using glass-ceramic coating is its ability to tune coating properties by changing the composition. Thus, future works are being carried out to alter the glass-ceramic composition to develop a potential TBC system.